Stallion Sperm Viability, as Measured by the Nucleocounter SP-100, Is Affected by Extender and Enhanced by Single Layer Centrifugation. (12th November 2009) - Morrell, J. M.; Johannisson, A.; Juntilla, L.; Rytty, K.; Bäckgren, L.; Dalin, A.-M.; Rodriguez-Martinez, H.
Abstract : On-stud assessment of stallion sperm quality can be problematic. A new instrument, the Nucleocounter SP-100, was validated for measuring stallion sperm concentration and viability. It was subsequently used to evaluate sperm viability in Kenney's extender and INRA96. There was a strong correlation between sperm concentrations measured by the Nucleocounter SP-100 and by the Bürker counting chamber (r = 0.84 ; P < .001 ). Similarly, there was a good correlation between sperm viability results from the Nucleocounter SP-100 and flow cytometric results (r = 0.73 ; P < .001 ). Sperm viability at 24 hours was significantly better for samples extended in INRA96 than in Kenney's extender (P < .001 ). Furthermore, sperm kinematics were better for stored samples in INRA96 than in Kenney's extender. Single Layer Centrifugation selected spermatozoa that maintained their viability better during storage for 24 hours than the uncentrifuged samples. In conclusion, the type of semen extender used and Single Layer Centrifugation were found to influence both the kinematics and viability of stallion spermatozoa. The Nucelocounter-SP100 was considered to be a useful instrument for rapidly measuring stallion sperm concentration and viability.